Information and energy aspects of analysis of complex coordination movements in archery - Лопатьєв, А. О.; Власов, А. П.; Трач, В. М. (Physical Education Theory and Methodology, 2013)
We consider complex coordination movements of archers as systems undergoing energy and information exchange processes. Connection between system entropy change and information input is employed during analysis. Examples are provided of cases when system entropy decreases with increase of information input.